Biotechnology towards energy crops - Gudeta Dida (CABI Agriculture and Bioscience)
Abstract Our world is experiencing an unprecedented surge in energy demand due to rapid economic growth and population expansion. This escalating need for energy poses a significant challenge as reliance on fossil fuels leads to severe environmental pollution. Consequently, the exploration of renewable energy sources, such as biofuels, emerges as a prudent solution to mitigate the energy crisis. The cultivation of novel crops and the implementation of advanced cultivation systems are gradually gaining traction, aiming to minimize dependence on depleting fossil fuel reserves and foster resilience to global climate change. These promising biological resources hold immense potential as bioenergy feedstocks, offering a versatile and sustainable means to meet the energy requirements of modern society on a daily basis. Biotechnology, in particular, can play a critical role in developing superior genotypes of energy crops, specifically tailored for efficient bioprocessing and subsequent utilization. By applying cutting-edge molecular techniques, a wide range of important traits can be enhanced, encompassing total biomass yield, production, quality, and resistance to different biotic and abiotic stresses. These advancements have the potential to significantly improve the efficiency, cost-effectiveness, and environmental benefits of biofuels. This comprehensive review aims to evaluate the potential of biotechnological applications in the development of advantageous bioenergy crops, spanning from feedstock enhancement to sustainable biofuel production. Furthermore, it provides compelling examples of cutting-edge research in the field, showcasing the prospects of energy crop innovation.